2010
DOI: 10.1097/qmh.0b013e3181eb13ab
|View full text |Cite
|
Sign up to set email alerts
|

A Physician Leadership Development Program at an Academic Medical Center

Abstract: To achieve care integration required for efficient high-quality care, physicians are increasingly organized into large multispecialty groups. The success of these groups depends in large part on the ability of leadership to successfully navigate the shifting reimbursement, regulatory, and quality and safety terrain, while simultaneously providing their physicians with a rewarding practice environment. The knowledge and management tools required for such leadership are not taught in medical school or residency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Furthermore, existing literature on leadership programs primarily describes the positive effects of a dedicated leadership curriculum on physician participants, including increased commitment to the parent organization, improved team building and interpersonal skills, and enhanced perspectives of leadership in their personal careers. 6, 14, 15 These prior studies did not present a detailed discussion of aspects of the program that participants found unhelpful or even wasteful. The results of the present study are corroborated by many of the positive findings from prior investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existing literature on leadership programs primarily describes the positive effects of a dedicated leadership curriculum on physician participants, including increased commitment to the parent organization, improved team building and interpersonal skills, and enhanced perspectives of leadership in their personal careers. 6, 14, 15 These prior studies did not present a detailed discussion of aspects of the program that participants found unhelpful or even wasteful. The results of the present study are corroborated by many of the positive findings from prior investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Their familiarity of the local health system also brought relevance to the concepts that were being taught. (Gagliano et al, 2010) We are likely delivering the curriculum to a highly motivated subgroup that may have been already selected or selfselected. However, the weekend and modular approach should minimize barriers.…”
Section: Discussionmentioning
confidence: 99%
“…(Jaffe et al, 2016) Some of the learning needs identified by physician leaders include: 1) financial planning, 2) conflict resolution and negotiation, 3) communication, 4) strategic analysis. (Gagliano et al, 2010) In recognition of the need for managerial acumen in physician leaders, several organizations have created their own in-house physician leadership training. (Tangalos et al, 1998;Stoller, Berkowitz and Bailin, 2007;Cherry, Davis and Thorndyke, 2010;Murdock and Brammer, 2011;Bircher, 2013;Clyne, Rapoza and George, 2015) Additionally, Medical associations and societies have also established physician leadership programs, with recognitions for completing of set of courses with demonstration of leadership accomplishments.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership development programs for senior health care leaders are well established within academic medical centres; however, the same dedicated mentorship opportunities for trainees are often lacking in medical school or residency training programs [1][2][3][4]. In fact, few medical schools and graduate medical education programs have a dedicated leadership curriculum in North America [5].…”
Section: Leadership Competencymentioning
confidence: 99%